Analysis of Scientific Field Suitability and the Goal Achievement of Certified Independent Study Internship and Learning Activity Form for Undergraduate Students of Social Science Education at Universitas Negeri Malang - David Golddra Pamungkas Bramantya; Neni Wahyuningtyas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The Form of Learning Activity (BKP) of the Certified Independent Study Internship (MSIB) is designed to provide students with direct exposure to the contemporary world of work. However, in its implementation, issues related to the achievement of BKP MSIB objectives and the alignment between BKP MSIB activities and students’ scientific fields of study have emerged as significant concerns. This study aims to describe the achievement of BKP MSIB objectives among undergraduate students of the Social Science Education Study Program at Universitas Negeri Malang (UM) and to examine the suitability of BKP MSIB activities undertaken by these students with their field of study. The research employs a descriptive narrative method based on the experiences of BKP MSIB participants from the undergraduate Social Science Education program at UM. The findings indicate that the objectives of BKP MSIB are generally achieved, as students gain meaningful experiential learning through participation in certified internships lasting one to four months and certified independent studies that involve real-world issues subsequently discussed in classroom settings. These experiences demonstrate that BKP MSIB effectively facilitates students’ exposure to professional practices and contextual problem-solving. Nevertheless, the study also reveals several shortcomings in its implementation, particularly the mismatch between BKP MSIB programs undertaken by students and the scientific field of Social Science Education. In addition, the findings indicate that some students participate in BKP MSIB due to a perceived sense of compulsion rather than intrinsic motivation, suggesting the need for improved program alignment, guidance, and flexibility to better accommodate students’ academic backgrounds and interests.